Electroencephalographic Theta-Band Oscillatory Dynamics Represent Attentional Bias to Subjective Preferences in Value-Based Decisions - Diao L; Li W; Zhang W; Ma Q; Jin J (Psychology Research and Behavior Management, 2021)
Liuting Diao,1,2 Wenping Li,3 Wuke Zhang,1,2 Qingguo Ma,1,2,4 Jia Jin5 1Business School, Ningbo University, Ningbo, People’s Republic of China; 2Academy of Neuroeconomics and Neuromanagement, Ningbo University, Ningbo, People’s Republic of China; 3Prudence College, Zhejiang Business Technology Institute, Ningbo, People’s Republic of China; 4School of Management, Zhejiang University, Hangzhou, People’s Republic of China; 5School of Business and Management, Shanghai International Studies University, Shanghai, People’s Republic of ChinaCorrespondence: Qingguo Ma; Jia Jin Email maqingguo3669@zju.edu.cn; jinjia@nbu.edu.cnBackground: Previous studies have shown that people always pay more attention to highly preferred items of choice, which is well defined by behavioral measurements and eye-tracking. However, less is known about the neural dynamics underlying the role that visual attention plays in value-based decisions, especially in those characterized by the “relative value” (ie, value difference) between two items displayed simultaneously in a binary choice.Purpose: This study examined the neural temporal and neural oscillatory features underlying selective attention to subjective preferences in value-based decision making.Methods: In this study, we recorded electroencephalography (EEG) measurements while participants performed a binary choice task in which they were instructed to respond to their preferred snack in high value difference (HVD) or low value difference (LVD) conditions.Results: Behaviorally, participants showed faster responses and lower error rates in the HVD condition than in the LVD condition. In parallel, participants exerted a reduced prefrontal N2 component and attenuated frontal theta-band synchronization in the HVD condition as opposed to the LVD condition. Crucially, participants showed greater N2pc component and theta-band synchronization over the human posterior cortex in the HVD condition than in the LVD condition. Moreover, there was a direct correlation between frontal and posterior theta-band synchronization.Conclusion: The results show that theta-band oscillatory dynamics may represent attentional bias to subjective preferences, and this effect can be modulated by the level attentional bias to subjective preferences, and this effect can be modulated by the level of value difference. Our research provides insights into a new avenue via which the processing of selective attention and value representation in the value-based decisions can be implicated in an integrative neural oscillatory mechanism.Keywords: theta-band synchronization, attentional bias, subjective preferences, value-based decision making, consumer neuroscience